Nas periferias do gênero: transitando entre hip hop, funk e feminismos - Larissa Amorim Borges (2013)
The present work is one of the possible systematization of an intense process of research and reflexivity developed from contact with young black women participating in Hip Hop and Funk in Belo Horizonte and Metropolitan Region. Reflecting on the ongoing research and the challenges of building knowledge from the perspectives of black feminism organized my thoughts on this militant-research in 4 (four) chapters, as follows: I - Building a research afrocentrada and peripheral; II - Feminisms and Gender Peripheries; III - Approaching the Field: Militancy, Epistemology, Methodology, and IV - Party Power: Why the pleasure of perifeira bother so much? The purpose of this paper is to share the knowledge accessed and produced during the process of the master and who knows, cause displacements and dialogues among young women social movements, cultural and academia and others. The discussions shared here are just the beginning of a long process of building knowledge about gender relations in the periphery, the interssecções possible racism and sexism in the lives of black youth and slum as well as the strategies of resistance to genocide and femicide built this youth.